2010
DOI: 10.4194/trjfas.2010.0208
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The Zn, Cu, As, Cd, Hg and Pb levels of the popular species (Silurus triostegus, Acanthobrama marmid, Aspius vorax, Capoeta trutta, Carasobarbus luteus, Chalcalburnus mossulens and Cyprinus carpio) of Ataturk Dam Lake (Euphrates, Turkey) were studied to estimate the risk of human consumption and pollution of Euphrates River which is important for Turkey, Syria and Iraq. Trace metal amounts differed between the species (P<0.05) even they were living in similar habitats. The variations of measured heavy metals (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 17 publications
0
2
1
Order By: Relevance
“…In contrast to our findings, De Rosemond et al [20] reported higher levels of As 0.42-2.25 µg g -1 in liver and 0.57 to 1.15 µg g -1 in muscle tissues of five freshwater fish species. Mol et al [21] reported comparatively lower As concentration (0.164-0.279 µg g -1 ) in muscles of freshwater fish species from Ataturk dam lake, Euphrates, Turkey as compared to our study.…”
Section: Resultscontrasting
confidence: 70%
“…In contrast to our findings, De Rosemond et al [20] reported higher levels of As 0.42-2.25 µg g -1 in liver and 0.57 to 1.15 µg g -1 in muscle tissues of five freshwater fish species. Mol et al [21] reported comparatively lower As concentration (0.164-0.279 µg g -1 ) in muscles of freshwater fish species from Ataturk dam lake, Euphrates, Turkey as compared to our study.…”
Section: Resultscontrasting
confidence: 70%
“…Cadmium is regarded as a priority pollutant because of its toxicity to organisms in the aquatic environment (Saddiq, 1992). When excess Cd is absorbed through sea food it tends to accumulate in the liver and in the kidneys of the human body ( Mol et al, 2010). The main sources of Cd in the present geographical location are electroplating and an important metal with many industrial applications.…”
Section: Discussionmentioning
confidence: 99%
“…A wide range of techniques have been used for determining of trace heavy metals such as inductively coupled plasmaatomic emission spectrometry (ICP-AES) 8 , inductively coupled plasma-mass spectrometry (ICP-MS) 9 , inductively coupled plasma-optical emission spectrometry (ICP-OES) 10 , X-ray fluorescence spectrometry, capillary electrophoresis (CE) 11 , atomic absorption spectrometry by graphite furnace (AAS-GF) 12 and Flame atomic absorption spectrometry (FAAS) 13 . Flame atomic absorption spectrometry (FAAS) has been shown to be a promising technique for the determination of trace heavy metals in view of its low costs and easy usage 14 .…”
Section: Introductionmentioning
confidence: 99%